Towards a redefinition of the concept community - Krause Jacob, Mariane (Revista de Psicología, 2001)
One of the problems community psychology has nowadays is the definition of community. Traditionally community psychology had inspired in a concept of community linked firmly to the territory (in the sense of geographic location). But now, at the beginning of a new hstorical era, the notion of territory of communities is vanishing, since there is an increasing development of social networks and groups who do not share a geographic location, even more, in some of them the members even don’t meet personally. Looking at this fact, one could state the necessity of redefining the concept of community. This new community-concept can exclude the notion of territory, but it has to be clear in other characteristics of a community, in order to differentiate it from other kind of human associations.This paper proposes a concept of community characterized by the inclusion of three elements: belonging (as the feeling of "being part of" and "identified with"); interrelation, that is: communication, interdependence, and mutual influence; and common culture, in the sense or the existence of shared meanings.